PERAN GURU DALAM PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION DI SEKOLAH DASAR - Dewanti, Rahayu; Ardhyantama, Vit; Qudsiyah, Khoirul (Scholarly Journal of Elementary School, 2025)
ABSTRACT This study aims to explores the role of teachers in cooperative learning of the group investigation type at SD Negeri Ploso 1, Pacitan. The role of teachers is examined in terms of inhibiting and supporting factors. This research employs a qualitative approach with descriptive methods. Data were obtained from class teachers and students from grades 1 to 6 through observation, interviews, questionnaires, and documentation. Data were analyzed using the Miles and Huberman model. Data validity was ensured through triangulation, which included technique, source, and time triangulation. Based on the data obtained, the roles of teachers include facilitator, organizer, educator, motivator, conservator, transmitter, transformer, evaluator, innovator, and role model. The inhibiting and supporting factors influencing the teacher's role in learning encompass differences in students' backgrounds that resonate or do not resonate within the social scope, the cooperative learning method of group investigation, teacher competence and planning related to professionalism and technical readiness in the applied learning, and the relationships among teachers, students, and parents concerning educational factors and family harmonization dynamics. Keywords: teacher roles, cooperative learning, group investigation